STUDENTS’ DIFFICULTIES IN ONLINE MATH LEARNING DURING PANDEMIC COVID 19 - Delyanti Azzumarito Pulungan; Heri Retnawati; Amat Jaedun (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Students' Mathematical Resilience when learning mathematics online during the Covid 19 pandemic must be identified. The goal is to ensure online learning does not harm students' mathematics learning outcomes. Various studies on students' mathematical resilience in offline mathematics learning have identified that mathematical resilience affects students' mathematical performance. This study investigated the resilience of students perceived by students, as well as those observed by teachers during online mathematics learning during the covid 19 pandemic. Research data were obtained from 22 students who studied math online. Using an open questionnaire and interviews, the data were analyzed. It was revealed that students had difficulties in understanding math material and completing tasks given by the teacher. It was also revealed that teachers had difficulty assessing students' mathematics learning outcomes objectively and transparently. Students also find it difficult to get support in online mathematics learning from teachers and families. Students find it difficult to adapt, low interest and motivation during online mathematics learning, even the teacher's limitations in controlling students' online learning strategies.